Effectiveness and Safety of Direct Oral Anticoagulants in Thai Patients with Atrial Fibrillation: A Real-World Retrospective Cohort Study. (October 2022) - Srikajornlarp, Saowaluk; Amnueypol, Montawatt; Vathesatogkit, Prin; Numthavaj, Pawin; Ungkanont, Artit; Likittanasombat, Khanchit; Pattanaprateep, Oraluck; Angchaisuksiri, Pantep; Boonyawat, Kochawan
Background: Direct oral anticoagulants (DOACs) are commonly used to prevent stroke and systemic embolism in patients with atrial fibrillation (AF). However, studies into their effectiveness and safety in the Thai population have so far been limited. Objectives: To study the effectiveness and safety of warfarin and DOACs among Thai AF patients Methods: A retrospective cohort study was conducted on AF patients at Ramathibodi Hospital from 2013 to 2018. All patients were followed for at least 1 year. Relevant clinical information was collected and compared between AF patient groups receiving warfarin, dabigatran, rivaroxaban, and apixaban. The primary outcome was a composite of major bleeding, ischemic stroke, and systemic thromboembolism. The secondary outcomes were all-cause mortality and disease-specific mortality caused by major bleeding, ischemic stroke, and systemic thromboembolism. Results: A total of 1680 AF patients were enrolled in the study (warfarin 1193, apixaban 140, dabigatran 193, rivaroxaban 114). The estimated incidence of composite outcome was 16% [95% CI, 14−18%] and 12.4% [95% CI, 9.4−15.3%] in the warfarin and DOAC group, respectively, given a number needed to treat of 28 [95% CI, 3−52]. Compared with warfarin, DOACs were associated with both lower rate of all-cause mortality (4.9% [22/447] vs 8% [98/1193]) and lower disease-specific mortality (0.4% [2/447] and 1% [12/1193]). Conclusions: This study suggests DOACs were associated with a lower risk of major bleeding, ischemic stroke, and systemic thromboembolism compared to warfarin in Thai patients with AF. Patients receiving DOAC also had a lower rate of all-cause mortality and disease-specific mortality.